(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study used a Structural Equation Modelling approach to examine the socioeconomic and cultural factors influencing the adoption of clean cooking energy in rural Ghana, specifically within the Bunkpurugu-Nakpanduri district. The study bridges a gap in the literature by combining the Diffusion of Innovations Theory and the Technology Acceptance Model, which tends to disregard cultural aspects in SEM analyses. The data was gathered using a mixed-methods approach that included 7 focus groups, interviews with 30 opinion leaders, and surveys with 500 women. SPSS, NVivo, and AMOS were used for Data analysis. Consistent with previous research, the results validate that adoption of clean cooking technology is significantly positively influenced by household income and education. Most importantly, the study finds that cultural norms play a key mediating role, demonstrating that, even when economic and educational limitations are taken into account, deeply rooted customs and social expectations pose a distinct challenge in the Ghanaian context. According to local hospital data, biomass dependence is linked to thousands of respiratory and other illnesses among women and children each year, underscoring the serious health effects of this practice. The study concludes that effective energy transition policies in Ghana's rural areas need to include culturally sensitive interventions in addition to subsidies and awareness campaigns. To achieve sustainable adoption, it is essential that community leaders be involved, that technology be tailored to local culinary customs, that targeted financial support be put in place, and that an integrated strategy be promoted that respects local culture while enhancing affordability and education.